Programming gestures simulator with statistical modeling - Doroshenko, А.Yu.; Novak, O.S. (Інститут програмних систем НАН України, 2017)
Well-known R system of statistical mod-eling is applied for creating a simulator of recognition of a fragment of the ges-ture language associated with movements of the fingers of human hand. The effectiveness of the use of statistical modeling system for fast recognition and prediction of gestures is demonstrated with an example of a game problem.